Systematic Review and Meta-Analysis on Management of Hemodialysis Catheter-Related Bacteremia - Aslam, Saima (J Am Soc Nephrol, 2014)
Hemodialysis catheter-related bacteremia is a common clinical problem with several management options. We performed a systematic review and meta-analysis to determine cure proportions with systemic antibiotics, antibiotic lock solution, and guidewire exchange. We searched databases and registries; conference proceedings from relevant medical societies; and article reference lists. Data regarding management approach, cure, follow-up, recurrence, complications, and microbiology were abstracted and pooled from 28 selected publications. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated from a mixed effects logistic regression model. In total, 1596 patients with tunneled hemodialysis catheter-related bacteremia were divided into groups on the basis of treatment with systemic antibiotics (n=697), antibiotic lock solution (n=546), or guidewire exchange (n=353). Antibiotic lock solution and guidewire exchange had similar cure proportions that were superior to systemic antibiotics alone (OR, 2.08; 95% CI, 1.25 to 3.45; P<0.01 for antibiotic lock solution; OR, 2.88; 95% CI, 1.82 to 4.55; P<0.001 for guidewire exchange versus systemic antibiotics). Cure proportions were highest for coagulase-negative staphylococci followed by gram-negative rods and Staphylococcus aureus. Among S. aureus infections, guidewire exchange led to a higher cure proportion than systemic antibiotics or antibiotic lock solution (OR, 3.33; 95% CI, 1.17 to 9.46; P=0.02; OR, 4.72; 95% CI, 1.79 to 12.46; P=0.002, respectively). Thus, results of this study suggest that tunneled hemodialysis catheter-related bacteremia should be treated with either guidewire exchange or antibiotic lock solution. Future studies should address prospectively whether one strategy is better than the other overall and for specific pathogens.